Dysregulation profile (DP) as a transdiagnostic psychopathological factor in clinically referred children – comparisons between disorders and latent structure. (2nd January 2022) - Wang, Biyao; Becker, Andreas; Kaelble, Christina; Rothenberger, Aribert; Uebel-von Sandersleben, Henrik
Abstract: Background: Dysregulation Profile (DP) describes the psychopathological construct of concurrent impairments in the ability to regulate emotion, behaviour, and cognition measured by the Child Behaviour Checklist (CBCL). Such transdiagnostic dimensions of psychopathology play an important role in addition to core symptoms of psychiatric diagnosis in clinical practice. Evaluation of DP in children with different mental disorders may improve our understanding and treatment of both contents. Methods: 911 clinically referred children between 6 and 18  years were investigated. The sample consisted of five 'pure' disorders groups, that is, tic disorder (TIC), anxiety disorder, obsessive compulsive disorder, depression, Attention Deficit Hyperactivity Disorder (ADHD), and two comorbid disorder group, that is, ADHD + TIC and ADHD + oppositional defiant disorder (ODD). DP level and latent structure were compared across groups. Results: The rate of severe/abnormal dysregulation rates varied from 15% to 44% when the 210 cut-off was used, and 5% to 18% when stringent cut-off was used (i.e. ≥70 on all DP-subscales). The most affected population were children with comorbid ADHD with ODD/TIC, while least were those with TIC only. Five different latent phenotypes of DP were found. Conclusion: DP above clinical cut-off level widely exists in clinically referred children in parallel to core symptoms of their diagnosis, especially among children with comorbidities. During clinical assessment it would be worth to clarify the role of DP-related problems within the general psychosocial impairment of the patient to improve a personalized approach.